Distinct Episodic Verbal Memory Profiles in Schizophrenia - Brazo, Perrine; Ilongo, Michaelle; Dollfus, Sonia (Behavioral sciences, 2013)
According to some authors, episodic memory impairment may be a feature shared by all schizophrenic patients, whereas others argue in favor of the mnesic heterogeneity. Our aims were to determine whether patients can be grouped based on according to their mnesic performances. The California Verbal Learning Test (CVLT), an episodic verbal learning test, was compared in 61 schizophrenic patients and 61 matched healthy subjects. The 32 indices were calculated using CVLT Scoring Software. This process allowed us to describe patients’ episodic processes in detail (encoding, storage, retrieval). We isolated one group with normative data, another showed impairment of both encoding and retrieval processes, and in the last one, only encoding process was impaired. As schizophrenia is heterogeneous with regard to episodic memory, impairments should not be considered as a common core to the various forms of the illness and it would be fruitful to systematically assess episodic processes in detail to take into account individual abilities and challenges.